1964
DOI: 10.1021/jf60131a027
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Factors in Fat, A Contribution to the Knowledge of the Structure of Two Hydropericardium-Producing Factors from a Toxic Fat

Abstract: Two compounds, previously isolated from a toxic feed fat and capable of producing hydropericardium in chicks, were further characterized. Mass and other spectral data indicate that they are isomers with the molecular formula C14H,,Cls. A procedure was developed for reductive dehalogenation of l -mg. quantities of chlorinated hydrocarbons, with the resulting saturated hydrocarbons being identified by gas chromatography. Application of this procedure to the toxic compounds produced from each of them a mixture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1966
1966
1983
1983

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…In the light of current knowledge on the absorbability of dioxins (Firestone et al, 1971) and the lack of information about the manner of administration of toxic compound, diet, strain of bird, and other factors, 5 ng. or less of toxic compound as reported by Wootton and Courchene (1964) may be toxic to the chick.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…In the light of current knowledge on the absorbability of dioxins (Firestone et al, 1971) and the lack of information about the manner of administration of toxic compound, diet, strain of bird, and other factors, 5 ng. or less of toxic compound as reported by Wootton and Courchene (1964) may be toxic to the chick.…”
Section: Resultsmentioning
confidence: 75%
“…polyhalogenated organic compound which, when administered to chicks, will elicit some or all of the characteristic symptoms previously reported to describe the chick edema disease (Allen and Lalich, 1962;Allen, 1964;Allen and Carstens, 1966;Flick et al, 1965aFlick et al, ,b, 1966Flick et al, , 1967Wootton and Courchene, 1964). From the data on total dioxins ingested by chicks (Table 2), it is apparent that chicks respond to intakes of 9 to 23 fig.…”
Section: Resultsmentioning
confidence: 87%
“…Wootton and his colleagues proposed that HPTF was a chlorinated hexahydrophenanthrene with the empirical formula CI4H10C16. Following the molecular identification herein reported, Wootton (1966) showed that a synthetic hexachlorinated dibenzo-p-dioxin, whose physical properties are remarkably similar to the isolated ct-3.17 material, does indeed produce the hydropericardium condition in chickens. *…”
Section: Introductionmentioning
confidence: 66%
“…), elevated HP (<2 u,g. ), and severe edema are suggestive that the CEF preparation was cleaner than the purified concentrate reported by Flick et al (1965), and is on the order of toxicity for the fractions reported by Wootton and Courchene (1964). SUMMARY The following short-term studies have been completed on the chick edema disease: effect of age and level of toxic fatty material on the hydropericardial response of day-old and week-old White Leghorn cockerels, recovery of chicks with the disease, and calculation of the amounts of chick edema factor ingested which resulted in 50% mortality.…”
Section: Resultsmentioning
confidence: 87%